Challenges and barriers in delivering instructional information literacy in Malaysian Higher Education: insights from knowledge professionals - Dzulkipli, Mohd Razif; Abu, Roziya; Shaifuddin, Norshila (Journal of Islamic, Social, Economics and Development, 2025)
Teaching librarians are academic librarians who serve academic libraries and are required to teach and deliver instructional information literacy sessions. However, teaching librarians face challenges and barriers in delivering instructional information literacy. This study implemented qualitative research consisting of two rounds of the modified Delphi method, involving ten knowledge professionals spread from teaching librarians, researchers, and academics. A thematic analysis was used in data analysis, and the findings identified five themes in the challenges and barriers: teaching, technology issues, information, sessions, and modules. Eight themes were generated for recommendations to overcome the challenges and barriers. To address these challenges, institutions can better support teaching librarians in their critical role in fostering information literacy skills.